Vhc1, a novel transporter belonging to the family of electroneutral cation-Cl(-) cotransporters, participates in the regulation of cation content and morphology of Saccharomyces cerevisiae vacuoles - Petrezselyova, Silvia; Kinclova-Zimmermannova, Olga; Sychrova, Hana (Biochimica et biophysica acta, 2013)
Cation-Cl(-) cotransporters (CCCs) are integral membrane proteins which catalyze the coordinated symport of Cl(-) with Na(+) and/or K(+) ions in plant and mammalian cells. Here we describe the first Saccharomyces cerevisiae CCC protein, encoded by the YBR235w open reading frame. Subcellular localization studies showed that this yeast CCC is targeted to the vacuolar membrane. Deletion of the YBR235w gene in a salt-sensitive strain (lacking the plasma-membrane cation exporters) resulted in an increased sensitivity to high KCl, altered vacuolar morphology control and decreased survival upon hyperosmotic shock. In addition, deletion of the YBR235w gene in a mutant strain deficient in K(+) uptake produced a significant growth advantage over the parental strain under K(+)-limiting conditions, and a hypersensitivity to the exogenous K(+)/H(+) exchanger nigericin. These results strongly suggest that we have identified a novel yeast vacuolar ion transporter mediating a K(+)-Cl(-) cotransport and playing a role in vacuolar osmoregulation. Considering its identified function, we propose to refer to the yeast YBR235w gene as VHC1 (vacuolar protein homologous to CCC family 1).
Keywords: Membrane Potentials; Saccharomyces cerevisiae Proteins; Genotype; fylogeneze; konfokální mikroskopie; fluorescenční mikroskopie; Saccharomyces cerevisiae; Osmotic Pressure; Phylogeny; vakuoly; Hydrogen-Ion Concentration; Electrochemistry; Vacuoles; kationty; Sorbitol; iontový transport; osmotický tlak; membránové potenciály; koncentrace vodíkových iontů; Microscopy, Confocal; Cations; Microscopy, Fluorescence; elektrochemie; otevřené čtecí rámce; Ion Transport; Symporters; Recombination, Genetic; Saccharomyces cerevisiae - proteiny; rekombinace genetická; DNA; Open Reading Frames; chloridy; symportéry; genotyp; Oligonucleotides; oligonukleotidy; nigericin; sorbitol; Chlorides; Nigericin